Influence of cropping systems and organic amendments on productivity and soil health at mid altitude of North East India - DAS, ANUP; PATEL, D P; KUMAR, MANOJ; G I, RAMKRUSHNA; NGACHAN, S V; LAYEK, JAYANTA; LYNGDOH, M (The Indian Journal of Agricultural Sciences, 2014)
Field experiments were conducted during 2006-07 to 2008-09 to assess the response of different cropping systems and organic amendments on productivity and soil health at mid altitude (950 m MSL) of Meghalaya. The treatments consisted of two rice based (rice (Oryza sativa L.) + soybean [Glycine max (L.) Merr.] - rapeseed, rice + soybean - tomato (Solanum lycopersicum L.) and two maize based (maize (Zea mays L.) + soybean - groundnut (Arachis hypogaea L.), maize + soybean- French bean (Phaseolus vulgaris L.)) cropping systems and five organic amendments, viz. farmyard manure (FYM), vermicompost (VC), local compost (LC), combined sources of nutrient (1/3 FYM +1/ 3 VC + 1/3 LC) and control (no manure) as sources of nutrient supply. Organic manures were applied on N-equivalent basis and phosphorus requirement was compensated through rock phosphate. The results revealed that the yield of different crops were maximum under combined sources of nutrient supply (CSN). Pooled (3 years) maize equivalent yield (MEY) was the highest under FYM followed by CSN and remained at par with each other. The pooled MEY under FYM and CSN were 171 % and 162 % higher than control, respectively. Among the cropping systems, maize + soybean - French bean recorded the highest MEY (28.78 t/ha). Total N, P and K uptake was maximum with CSN and remained similar with FYM. Maximum bulk density, soil organic carbon, soil microbial biomass carbon, dehydrogenase enzyme activity, available N and K in soil after three cropping cycles were also recorded under CSN. Maize + soybean - French bean cropping system along with FYM as source of nutrient supply was found to be cost effective with optimum productivity during transition to organic farming.